Intoxication by gamma hydroxybutyrate and related analogues: Clinical characteristics and comparison between pure intoxication and that combined with other substances of abuse. (5th August 2017) - Miró, Òscar; Galicia, Miguel; Dargan, Paul; Dines, Alison M.; Giraudon, Isabelle; Heyerdahl, Fridtjof; Hovda, Knut E.; Yates, Christopher; Wood, David M.; Liakoni, Evangelia; Liechti, Matthias; Jürgens, Gesche; et al.
Highlights: The 78.0% of patients were over 24 years of age (median 31 years) and 83.4% were men. The most co-used substances: ethanol, amphetamine and derivatives, cocaine, benzodiazepines. The most common symptoms: behaviour altered, agitation and reduced level of consciousness. Endotracheal intubation and mechanical ventilation was performed in 6.9% of the whole group. The GHB/GBL with co-intoxicants group have more severe symptoms and higher necessity of therapy. Abstract: Objective: To study the profile of European gamma-hydroxybutyrate (GHB) and gammabutyrolactone (GBL) intoxication and analyse the differences in the clinical manifestations produced by intoxication by GHB/GBL alone and in combination with other substances of abuse. Method: We prospectively collected data on all the patients attended in the Emergency Departments (ED) of the centres participating in the Euro-DEN network over 12 months (October 2013 to September 2014) with a primary presenting complaint of drug intoxication (excluding ethanol alone) and registered the epidemiological and clinical data and outcomes. Results: We included 710 cases (83% males, mean age 31 years), representing 12.6% of the total cases attended for drug intoxication. Of these, 73.5% arrived at the ED by ambulance, predominantly during weekend, and 71.7% consumed GHB/GBL in combination with other substances of abuse, the most frequent additional agents being ethanol (50%), amphetamine derivatives (36%), cocaine (12%) and cannabis (8%). Among 15 clinical features pre-defined in the project database, the 3 most frequently identified were altered behaviour (39%), reduced consciousness (34%) and anxiety (14%). The severity ranged from mild cases requiring no treatment (308 cases, 43.4%) to severe cases requiring admission to intensive care (103 cases, 14.6%) and mechanical ventilation (49 cases, 6.9%). No deaths were reported. In comparison with only GHB/GBL consumption, patients consuming GHB/GBL with co-intoxicants presented more vomiting (15% vs. 3%, p < 0.001) and cardiovascular symptoms (5.3% vs. 1.5%, p < 0.05), a greater need for treatment (59.8% vs. 48.3%, p < 0.01) and a longer ED stay (11.3% vs. 3.6% patients with ED stay >12 h, p < 0.01). Conclusions: The profile of the typical GHB/GBL-intoxicated European is a young male, requiring care for altered behaviour and reduced level of consciousness, mainly during the weekend. The clinical features are more severe when GHB is consumed in combination with other substances of abuse.